Brain metastases in patients with EGFR-mutated or ALK-rearranged non-small-cell lung cancers. Issue 1 (April 2015) - Rangachari, Deepa; Yamaguchi, Norihiro; VanderLaan, Paul A.; Folch, Erik; Mahadevan, Anand; Floyd, Scott R.; Uhlmann, Erik J.; Wong, Eric T.; Dahlberg, Suzanne E.; Huberman, Mark S.; Costa, Daniel B.
Highlights: Brain metastases are frequent in ALK rearranged lung cancers. Brain metastases are frequent in EGFR mutated lung cancers. ∼25% of patients at diagnosis and half at 3-years of survival have brain metastases. Abstract: Introduction: Brain metastases (BM) are common in non-small-cell lung cancer (NSCLC). However, the baseline incidence and evolution of BM over time in oncogene-driven NSCLCs are seldom reported. In this study, we evaluated the frequency of BM in patients with epidermal growth factor receptor ( EGFR )-mutated or anaplastic lymphoma kinase ( ALK )-rearranged NSCLC. Methods: The presence of BM, clinicopathologic data, and tumor genotype were retrospectively compiled and analyzed from a cohort of 381 patients. Results: We identified 86 EGFR -mutated (90.7% with metastatic disease; 85.9% received an EGFR inhibitor) and 23 ALK -rearranged (91.3% with metastatic disease; 85.7% received an ALK inhibitor) NSCLCs. BM were present in 24.4% of EGFR -mutated and 23.8% of ALK -rearranged NSCLCs at the time of diagnosis of advanced disease. This study did not demonstrate a difference in the cumulative incidence of BM over time between the two cohorts (EGFR/ALK cohort competing risk regression [CRR] coefficient of 0.78 [95% CI 0.44–1.39], p  = 0.41). In still living patients with advanced EGFR -mutated NSCLC, 34.2% had BM at 1 year, 38.4% at 2 years, 46.7% at 3 years, 48.7% at 4 years, and 52.9% at 5 years. In still living patients with advanced ALK -rearranged NSCLC, 23.8% had BM at 1 year, 45.5% at 2 years, and 58.4% at 3 years. Conclusions: BM are frequent in advanced EGFR -mutated or ALK -rearranged NSCLCs, with an estimated >45% of patients with CNS involvement by three years of survival with the use of targeted therapies. These data point toward the CNS as an important unmet clinical need in the evolving schema for personalized care in NSCLC.